1995
DOI: 10.1250/ast.16.213
|View full text |Cite
|
Sign up to set email alerts
|

Active acoustic power control of a single primary and two secondary sources by the acoustic nodal point method.

Abstract: An active acoustic power control method for three-dimensional space was investigated both theoretically and experimentally. In this paper, the focus is on the typical case of a single primary and two secondary point sources, and methods of minimizing the power output were considered. Suitable arrangements of the sources and microphone were proposed on the basis of theoretical estimations. The authors call this the acoustic nodal point method. The power reducing performance was verified by applying the method t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…5 For active control systems with two secondary sources and one error microphone, it was shown that the error microphone should be placed between the monopole primary source and one secondary source and the optimal distance ratio should be 0.618 for the best performance. 12 The experimental results with a 4-channel active sound radiation control system demonstrated that placing the error sensors in the optimal near-field locations results in significant noise reduction and other error sensor displacements may also provide appreciable far-field attenuation considering the practical a) Electronic mail: jctao@nju.edu.cn behavior of sound sources and error sensors. 13 Genetic searching algorithms have been employed to optimize the locations of ten error microphones in an 8-channel active transformer noise control system to achieve global noise reduction at 100 and 200 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…5 For active control systems with two secondary sources and one error microphone, it was shown that the error microphone should be placed between the monopole primary source and one secondary source and the optimal distance ratio should be 0.618 for the best performance. 12 The experimental results with a 4-channel active sound radiation control system demonstrated that placing the error sensors in the optimal near-field locations results in significant noise reduction and other error sensor displacements may also provide appreciable far-field attenuation considering the practical a) Electronic mail: jctao@nju.edu.cn behavior of sound sources and error sensors. 13 Genetic searching algorithms have been employed to optimize the locations of ten error microphones in an 8-channel active transformer noise control system to achieve global noise reduction at 100 and 200 Hz.…”
Section: Introductionmentioning
confidence: 99%